COLD, INCLUDING MISSILE, WEAPONS AS THE CRIME MEANS BY THE RUSSIAN CRIMINAL LAW - I. I. Bikeyev (Russian Journal of Economics and Law)
In the modern Russian criminal situation the illegal use and application of cold, including missile, weapons is widely spread. The article, based on the analysis of published scientific viewpoints, contains author's conclusions and suggestions on the determination and features of such weapons as a means of crime, their classification and changing of the actual law.